Perkembangan Pranata Sosial Berbasis Hukum Keluarga Islam di Indonesia - Hafiz, Abdul (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2014)
Islamic teachingpreached by Muhammad saw contained verious norms- moral norm, legal norm, and social norm- have beeninstitutionalized in the Islamic community as well as partly transformed into social institutions. The morerevelations received by Muhammad the more norms conveyed to humans, and the more types of socialinstitutions arise. When Muhammad was in Mecca while performing education institutions, he focused hisattention on engrafting social norms. Dealing with marriage circumstances, a lot of changes of legal normswere regulated by the Marriage Code of Number 1 1974. The changes do not mean an old thing changes to newor a current thing differs from the past. The change often means to replace something to another one whichhas been exactly existed but not popular. Allowing woman becomes a judge, for instance, is one of the lawchanges that the former law did not allow her as a judge because of following certain sect. According to othersects, such allowing is not something new, but it has been existed since classical Islamic era. The change alsomeans adopting certain concept and it is modified then. Adopted child is forbidden in Islam, but the Islamic LegalCompilation allowed it with modification.